Privacy Protection on Cloud Computing with Auditing Scheme - Manuel, Nimmymol; Mary Kurian, Simy; Joseph, Neena; George, Neema (International Journal of Computer Sciences and Engineering, 2025)
Distributed computing gives an assortment of administrations to our current specialized regions. It is helpful for the two customers and organizations to utilize applications without access their own records. Security is an unavoidable component of our cloud administration. So we ought to make sure that our specialist organization can give the security to our information. Yet, various prominent hacking cases will prompt various sorts of safety issues on cloud. It for the most part happens in multi clients distributed computing regions Cloud security is significant in each field of clients. Everybody needs to give their data completely safe. For this reason, here we can utilize property-based encryption that is a kind of open key encryption. Characteristic based encryption permits information proprietors and clients to encode and decode in light of the individual ascribes. So we propose a audit scheme which gives a sort of security insurance on clients and keep from unapproved access from programmers.